Exploration and implication of green macroalgal proliferation in the Nanhui-east-tidal-flat: an investigation of post-reclamation mudflat wetlands - Jinlin Liu; Zhangyi Xia; Yinqing Zeng; Jing Xia; Jing Xia; Peimin He (Frontiers in Marine Science)
The Nanhui-east-tidal-flat (NETF), the largest marginal shoal in the Yangtze River of China, is significantly impacted by human activities. Prior research has not detected the presence of green macroalgae in the NETF, nor has it explored the effects of reclamation on the distribution of macroalgae. However, in 2021, a small-scale aggregated attached algal mats emerged in the NETF, potentially signaling the onset of a green tide and necessitating vigilant monitoring. Morphological and molecular biological identification analysis revealed that all collected green macroalgae were attributed to a single dominant species, Ulva prolifera, characterized by broad blades and prominent air bladders, colonizing various substrates. The attached U. prolifera exhibited continuous growth from March to May 2021, peaking at a wet weight of 373.6229 g/m² and a dry weight of 72.7904 g/m² on May 1, 2021, within the accessible sampling period. The rapid proliferation of the “opportunistic” Ulva was facilitated by high-level eutrophication and favorable environmental conditions. Furthermore, six potential germplasm sources of U. prolifera are summarized. The dominance of Ulva in the intertidal zone often indicates high eutrophication and deteriorating ecological conditions. With long-term reclamation and repeated ecological restoration projects, the intertidal vegetation is subjected to a vicious cycle of growth and destruction. Therefore, it is important to recognize that U. prolifera germplasm (macroalgae and micropropagules) will persist over the long term, and mudflats with monotonous and eutrophic habitats are highly likely to experience future large-scale algal blooms. Notably, a small-scale floating green tide was observed in the sea area near NETF in July 2023, and such concerns are not unfounded. This study conducts foundational scientific research on the attached green tide algae, a type of research that is relatively scarce in other marine areas. Most studies tend to initiate foundational research only after the outbreak of green tides, lacking early background data from the marine environment, thus rendering this study of significant reference value. Concurrently, this study emphasizes that field surveys remain an essential approach for conducting foundational scientific research on green tide algae in the NETF region, with the need to select appropriate research methods based on the occurrence and development of algal mats, as required by the situation. Importantly, this study reflects the stability of marine ecosystems as a prerequisite for modern ocean management and services, provides new perspectives on the occurrence and development of green tides, and highlights potential ecological risk factors that should be considered in the implementation of intertidal construction projects.